Unintended positive and negative effects of drugs on lipoproteins. Issue 4 (August 2015) - Siahmansur, Tarza J.; Schofield, Jonathan D.; Azmi, Shazli; Liu, Yifen; Durrington, Paul N.; Soran, Handrean
<x xml:space="preserve">Abstract</x> Purpose of review Dyslipidaemia is an important cardiovascular disease risk factor. Many drugs affect lipid profile and lipoprotein metabolism. We reviewed unintended effects of nonlipid modifying, commonly used medications on lipid profile and lipoprotein metabolism. Recent finding Several detrimental effects of many drug classes such as diuretics, antidepressant, anticonvulsant and antiretroviral drugs have been reported, whereas other drug classes such as antiobesity, alpha 1-blockers, oestrogens and thyroid replacement therapy were associated with positive effects. Summary Dyslipidaemia is a common side-effect of many medications. This should be taken into consideration, especially in patients at high risk of cardiovascular disease. Other drugs demonstrated positive effects on circulating lipids and lipoproteins. The impact of these unintended effects on atherosclerotic disease risk and progression is unclear.